On lithospheric flexure seaward of the Bonin and Mariana trenches - Bodine, J; Watts, A (1979)
More than 25 bathymetry profiles have been used to examine the flexure of the Pacific lithosphere seaward of the Izu-Bonin and Mariana trenches. Selected bathymetry profiles have been corrected for the effects of sediment loading and compared to simple elastic and elastic-plastic models for lithospheric flexure seaward of these trenches. Profiles of the northern Mariana trench, where the seaward wall is relatively gentle, can be explained by a simple elastic model without an applied horizontal load. Profiles of the Izu-Bonin and southern Mariana trenches, where the seaward wall is relatively steep, can be explained by an elastic-plastic model with an applied load of 4.0-6.0 kbar, depending on the uniform yield stress assumed. If it is assumed the yield stress varies with depth the horizontal load required is significantly reduced (≲2.5 kbar). The magnitude of the horizontal load cannot be determined with certainty, however, since it is not known how the yield stress may vary with depth. The elastic-plastic models examined all required significant differences (∼1.0 kbar) in the horizontal load along the Izu-Bonin and Mariana trenches. These differences, which reach a maximum between the northern Izu-Bonin and northern Mariana trenches, appear to correlate with changes in the pattern of seismicity and tectonics landward of these trenches. © 1979.